1994
DOI: 10.1002/ijc.2910590414
|View full text |Cite
|
Sign up to set email alerts
|

Changes in p53 and cyclin D1 protein levels and cell proliferation in different stages of human esophageal and gastric‐cardia carcinogenesis

Abstract: The objective of this study was to quantify the changes in p53 and cyclin D1 protein levels in different stages of human esophageal and gastric cardia carcinogenesis in a high-risk population in Henan, China. Immunoreactivity of p53, cyclin D1 and proliferating-cell nuclear antigen (PCNA) was observed in the cell nuclei of esophageal and gastric cardia biopsies. The number of p53-immunostaining-positive cells was low in normal epithelia, slightly increased in basal-cell hyperplasia (BCH), markedly increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 14 publications
3
61
0
1
Order By: Relevance
“…42 Further support for the notion that cyclin D1 alterations occur relatively early in carcinogenesis is derived from a related study of premalignant lesions of the upper aerodigestive tract, in which cyclin D1 overexpression was observed in 14 of 28 dysplastic lesions (50%) that were localized to the basal and parabasal layers. 43 Despite chemoprevention with retinoids, cyclin D1 expression was not altered in 12 of 14 patients, with 8 patients showing histologic progression to invasive carcinoma on follow-up biopsies.…”
Section: Discussionmentioning
confidence: 97%
“…42 Further support for the notion that cyclin D1 alterations occur relatively early in carcinogenesis is derived from a related study of premalignant lesions of the upper aerodigestive tract, in which cyclin D1 overexpression was observed in 14 of 28 dysplastic lesions (50%) that were localized to the basal and parabasal layers. 43 Despite chemoprevention with retinoids, cyclin D1 expression was not altered in 12 of 14 patients, with 8 patients showing histologic progression to invasive carcinoma on follow-up biopsies.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulation of this complex leads to the activation of the kinases that phosphorylate and inactivate the tumor suppressor retinoblastoma, a necessary step for cell cycle progression through G1-to-S phases (Harbour and Dean, 2000). The expression levels of cyclin D1 have been shown to be rate limiting in cellular proliferation induced by a variety of stimuli (Ohtsubo and Roberts, 1993;Quelle et al, 1993;Albanese et al, 1995;Watanabe et al, 1996), and an increased expression of cyclin D1 has been observed in several tumors (Wang et al, 1994;Arber et al, 1996;Zhang et al, 1997;Albanese et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In China, epidemiologically, gastric cardia adenocarcinoma (GCA) shares a very similar geographic distribution with esophageal squamous cell carcinoma (SCC), especially in Linzhou (formerly Linxian County), Henan Province, north China, the highest incidence area of SCC in the world [1,2] . However, the incidence of adenocarcinoma arising from the distal stomach is very low in this area [3,4] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%